Apresiasi Keimanan kepada Tuhan melalui Pengalaman Spiritual - Abdul Kadir (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2015)
The awareness of God departed from religion which becomes introverted understanding in one’s experience. Appreciation of God should not be limited to formalities’ value by simply doing spirituality teaching and the embodiment of God’s spiritual experience. The constellation of religious values is not just about understanding and appreciation but also about achieving esoteric experience to reveal its meaning for deeper appreciation, recognition, and encounter with Him. The esoteric aspect of religion has become an important goal in the appreciation of spiritual experience ascent and acquisition with cleaning bonds which related to plurality and turned it from horizontal dimension senses to the vertical dimension of the universe to reach the consciousness of mortality. If God wills, there will be an incline in spiritual sensing sharpness until one can see, watch, or feel the real evidence from God about the things that are obviously high, so that the faith-based on mukâshafa, ma‘rifa, and mushâhada namely faith through a spiritual vision to arrive at the essence.